A comment on "The Effects of Racial Diversity in Citizen Decision-Making Bodies" - Do Won Kim; Xilin Yang; Do-Hoon Kim (Institute for Replication (I4R), 2024)
Karpowitz et al. (2024) examine the effect of racial diversity on group decisionmaking. The authors used OLS regression to analyze 2,694 citizens randomly assigned to 449 mock juries who are tasked to make decisions, and they find that the number of the people of color (POC) affects private decisions, but not so much on group decisions. We successfully replicated the main results of the paper with no coding errors, and we implemented the following robustness checks. First, we reset different seeds and found that they do not change the tables or the graphs, so the findings are not subject to arbitrarily chosen seed. Second, we applied multiple imputations rather than list-wise deletion for a few variables which the authors removed for containing missing values. While the original result continues to hold, our findings suggest that the presence or absence of even one individual of POC on the jury might be more significant than the incremental increases of the number of POC on the jury. Third, we shifted from using POC as the independent variable to using Black as the binary independent variable. When the group's racial composition is framed as Black versus non-Black, we do not observe a significant impact on individual punitiveness after deliberation. In addition, juries with one or no Black members showed greater punitiveness in their initial verdicts compared to juries with two or more Black members, but this effect diminished by the second round.
Keywords: 330; OLS Regression; Robustness Testing